Introduction to information optics - Yu, Francis T. S. 1932-; Jutamulia, Suganda.; Yin, Shizhuo, 1963- (Optics and photonics., 2001)
While there are books treating individual topics contained in this book, this will be the first single volume providing a cohesive treatment on this subject as a whole. This goes beyond optical communications in that it includes related topics such as sensing, displays, computing, and data storage.